Martín López, conquistador citizen of Mexico. - Gardiner, C. Harvey (Clinton Harvey) (University of Kentucky Press, 1958)
In this study of the life of a Spaniard who came to Mexico as a conquistador and remained as a civilian citizen of New Spain, C. Harvey Gardiner gives his readers a fresh view of the warfare between Spaniard and Indian and of the less dramatic processes of colonization which established European culture in America. Conquest and colonization, usually treated separately in the histories of the period, are here shown as phases in the life of a man who was not conspicuous among the conquerors, but was representative of the Spaniards of his generation who came to the new world in search of opportuni.